Treatment satisfaction and safety of sitagliptin versus pioglitazone in patients with type 2 diabetes mellitus inadequately controlled on metformin monotherapy - Haque, Shahnaz; Shukla, Anand; Kem, Anil (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study was designed to assess the treatment satisfaction between Sitagliptin versus Pioglitazone added to Metformin in patients with type 2 diabetes mellitus (T2DM). Methods: We conducted a prospective, open label, randomized, parallel group study in SIMS, Hapur, U.P. Eligible patients fulfilling inclusion criteria were randomized into two groups having 25 patients in each group using tab Sitagliptin 100mg,tab Pioglitazone 30mg added to ongoing tab Metformin (500mg) therapy for 16 weeks. The follow-up visits were on weeks 4, 12 and 16. Results: 16 weeks later, addition of Sitagliptin 100mg compared to that of Pioglitazone 30mg to ongoing Metformin therapy provided similar glycosylated haemoglobin (HbA1c) lowering efficacy in patients with T2DM with inadequate glycemic control on metformin monotherapy. Change in HbA1c in group1 was -0.656±0.21% (p<0.0001) whereas in group 2 was -0.748±0.35% (p<0.0001). Hence decrease in HbA1c from baseline was more in group2.Both treatments were well tolerated with negligible risk of hypoglycaemia. Weight loss was observed with Sitagliptin in contrast to weight gain seen in Pioglitazone. Conclusions: In this study, Sitagliptin 100 mg along with metformin therapy in comparison to pioglitazone 30 mg plus metformin therapy was effective, well-tolerated and improved glycemic control in both the groups. Addition of pioglitazone had cause oedema and weight gain to the patients whereas sitagliptin caused weight loss in its patients.